Surface modification on oil palm frond by sodium hydroxide and its effects on polypropylene composite properties / Nor Farhana Jasmi - Jasmi, Nor Farhana (2019)
This research aim is to study the effects of Sodium Hydroxide (NaOH) treatment on oil palm (Elaeis guineensis) frond particle surface that influence the properties of the treated particle-polypropylene composite. Samplings were divided into three major parts, which are i) Part I: Effects of particle size and filler loading, ii) Part II: Effect of addition of Maleic Anhydride and iii) Part III: Effect of NaOH treatment on the composite. In Part I, particle size do play significant role in determining the mechanical and water absorption characteristics of the composite. It is observed that the particle size of 250 and 425μm have contributed in better performance of mechanical properties but not to water absorption. Large particle size has led to the increasing of water absorption behaviour and this might be due to the void spaces exist on the filler surface. Hence, the study then is intended to improve the interfacial adhesion between the oil palm frond filler and polypropylene to reduce the voids problem. Looking at the effect of filler loading, high filler loading has resulted in weakening the properties of the composite. Coupling agent of Maleic Anhydride Polypropylene was used with intention to improve the properties. Part II evaluated the effect of Maleic Anhydride Polypropylene (MAPP) as coupling agent on the composite performances. It was observed that 3% MAPP contribute at its best on the composite with high filler loading of 50wt% as compared to the low filler loading of 10wt%. This may be attributed to the inadequate amount of 10wt% filler to receive the crosslinking action by MAPP. Part III discussed the effect of NaOH treatment on the oil palm frond-polypropylene composite with and without the coupling agent. Composites that filled with the treated filler and cross-linked with coupling agent exhibit better performance in mechanical properties and water absorption behavior. Regression analysis has proved the positive trend of composite properties performance when the filler was treated with NaOH. The R2 of all the derived equations for each board properties at 50wt% filler loading were above 60% without any exception. This showed a strong relationship between NaOH treatment, MAPP addition and the OPF-PP composite properties. Morphological study of Scanning Electron Micrographs viewed the oil palm frond particle surfaces before and after treatment. It is observed that the clogging of unwanted cementing materials on the treated particles were reduced leaving the cell cavity hollow and clean. Scanning on the composite fractured surface showed some reductions of pull outs when the filler was treated with the help of crosslinking action by Maleic Anhydride. Fourier Transform Infrared has detected some functional groups corresponding to the effect of NaOH treatment and the addition of the coupling agent.